Gender, Faith, and Reform: A Narrative Review of Islamic Feminism and Public Policy - Rofiq, Nur (Yayasan Sinergi Kawula Muda, 2024)
The discourse on gender in Islam has gained increasing scholarly attention due to its profound implications for justice, human rights, and societal development in Muslim-majority contexts. This study aims to examine how Islamic thought has addressed gender through various interpretative approaches and the role of legal, institutional, and political systems in shaping these discourses. Using a narrative review methodology, literature was systematically sourced from major academic databases including JSTOR, Scopus, and Google Scholar. Keywords such as